Contextual-STEM-Based E-Module Development in Enhancing Junior High School Students’ Mathematical Reasoning Abilities - Arifin, Sujinal; Efriani, Arvin; Cintania, Wella; Komarudin, Komarudin (Jurnal Pendidikan MIPA, 2025)
The disconnect between mathematics content and real-world applications creates significant challenges for students' understanding of fraction operations, resulting in procedural learning without conceptual depth. This study develops and evaluates a STEM-based e-module integrating authentic contexts with systematic instructional design to enhance junior high school students' mathematical reasoning abilities. The research employed the ADDIE development model to create a STEM-based e-module on fraction operations using snack nutritional values as context. The Engineering Design Process (EDP) served as the central pedagogical framework, structuring activities through seven systematic stages: Define, Research, Plan, Create, Communicate, Redesign, and Evaluate, transforming abstract mathematical concepts into meaningful problem-solving experiences. Three experts validated the e-module across five dimensions: content feasibility, presentation quality, language appropriateness, practicality, and STEM integration. Practicality testing involved progressive trials: one-to-one (3 students), small group (6 students), and field implementation (30 students). Mathematical reasoning effectiveness was measured using contextual problem-solving assessments evaluating five indicators: conjecturing, pattern identification, mathematical manipulation, justification provision, and conclusion drawing. Validation results demonstrated exceptional quality, with the e-module achieving a 95.2% overall validity index. Practicality testing revealed an average satisfaction of 90.28%, categorized as "very practical." Students demonstrated substantial improvement in mathematical reasoning, with an average final assessment score of 77.68. Students performed strongest in drawing conclusions (87%) and providing justification (81.67%), while conjecturing achieved a rate of 64%. Qualitative analysis revealed that while high-ability students employed formal reasoning and symbolic representation, some medium-ability students relied more on narrative responses, reflecting a gap between intuitive understanding and formal expression. The study concludes that the developed e-module is valid, practical, and effective in fostering students' mathematical reasoning. Integrating EDP into STEM-based e-modules provides a promising pathway to bridge procedural knowledge and conceptual depth, promoting meaningful and transferable learning experiences.    Keywords: contextual learning, engineering design, fractions context, mathematical reasoning, STEM e-module.